Rancang Bangun Palang Pintu Keamanan Rel Kereta Api Otomatis Berbasis Android - Juli Exno; Guslendra; Romi Wijaya (Journal of Computer Scine and Information Technology, 2023)
Train accidents are one of the transportation events that often occur in Indonesia. One of the problems that surfaced is the problem of railroad crossings. Accidents that often occur around railroad crossings are caused by the negligence of gatekeepers or the attitude of undisciplined drivers. In order to reduce these accidents, it is necessary to provide automatic crossings at unguarded crossings. Meanwhile, on guarded crossings, automatic door controls are installed to reduce human error, but can still be controlled manually when needed.In addition, the installation of manual passage gates at each railroad crossing will require a large amount of manpower. And on the crossbar draft. Automatic doors that previously used ultrasonic sensors were quite effective but were still constrained by ultrasonic sensors not being able to identify what objects were in front of them. Therefore, technology is needed to reduce accident rates at railroad crossings, as well as reduce accidents caused by (human error), provide educational facilities at each railroad crossing which are useful for increasing driver awareness so as not to cross railroad crossings when the gate is closed. cover and added an alert system to minimize sensor detection errors. The technology is a passageway that operates automatically and displays an LCD and speaker as a means of information.